Micro-particle chrominance automatic clustering analysis system - CHEN LIANGYI; WANG KAN; JIANG TIANLUN (2017)
A micro-particle chrominance automatic clustering analysis system comprises a large-area color micro-particle plane image acquisition system and a micro-particle chrominance clustering counting system. The large-area color micro-particle plane image acquisition system comprises a large field-of-view microscopy system, and a large-target-surface camera. The large field-of-view microscopy system images large-area color particles on the image sensor of the large-target-surface camera. The large-target-surface camera converts an optical signal received by the image sensor into a computer image. The micro-particle chrominance clustering counting system subjects the computer image to micro-particle image segmentation and chrominance recognition, performs clustering statistics based on the chrominance of the micro-particles, and outputs statistical information of the large-area color micro particles for analysis. 种微粒子色度自动聚类分析系统，包括大面积彩色微粒子平面图像采集系统，及微粒子色度聚类计数系统；大面积彩色微粒子平面图像采集系统，包括大视场显微系统、大靶面相机；大视场显微系统将大面积彩色微粒子成像于大靶面相机